Dhobi Ghat at Banganga - Ghosh, Ayan (2023)
A little away from Banganga Tank, on Dr. Bhagwanlal Indrajit Marg, is the local Dhobi Ghat. Dhobis wash the clothes manually using water from a deep well. Laundry is dried in the sea breeze and hung on cable lines without using clips, instead they are twined between cables.